Customer satisfaction : case study on CARREFOUR. - Koh, Hwee Ming. (2008)
This study is conducted to understand how foreign supermarket companies such as Carrefour are faring in their efforts to achieve customer satisfaction in Singapore. Carrefour is evaluated against the five factors which we believed would contribute towards determining the level of customer satisfaction among its customers.